Application of Electroporation Technique in Biofuel Processing - Yousuf, Abu; Khan, Maksudur R.; Islam, M. Amirul; Monir, Md Minhaj Uddin; Zularisam, A. W.; Pirozzi, Domenico (EDP Sciences, 2017)
Biofuels production is mostly oriented with fermentation process, which requires fermentable sugar as nutrient for microbial growth. Lignocellulosic biomass (LCB) represents the most attractive, low-cost feedstock for biofuel production, it is now arousing great interest. The cellulose that is embedded in the lignin matrix has an insoluble, highly-crystalline structure, so it is difficult to hydrolyze into fermentable sugar or cell protein. On the other hand, microbial lipid has been studying as substitute of plant oils or animal fat to produce biodiesel. It is still a great challenge to extract maximum lipid from microbial cells (yeast, fungi, algae) investing minimum energy. Electroporation (EP) of LCB results a significant increase in cell conductivity and permeability caused due to the application of an external electric field. EP is required to alter the size and structure of the biomass, to reduce the cellulose crystallinity, and increase their porosity as well as chemical composition, so that the hydrolysis of the carbohydrate fraction to monomeric sugars can be achieved rapidly and with greater yields. Furthermore, EP has a great potential to disrupt the microbial cell walls within few seconds to bring out the intracellular materials (lipid) to the solution. Therefore, this study aims to describe the challenges and prospect of application of EP technique in biofuels processing.